"They are not alone": Mentoring women graduate students. Issue 5 (26th September 2022) - Griffith, Emily; Sharp, Julia
Abstract : Women and other historically marginalised groups can feel out of place on advanced degree programmes – mentoring can help. Here, Emily Griffith and Julia Sharp – both winners of the Outstanding Mentor Award from the ASA's Statistical Consulting section – show how Abstract : Women and other historically marginalised groups can feel out of place on advanced degree programmes – mentoring can help. Here, Emily Griffith and Julia Sharp – both winners of the Outstanding Mentor Award from the ASA's Statistical Consulting section – show how